Epidemiology of pediatric patients admitted to a burns ICU in Saudi Arabia. Issue 3 (July 2020) - Akkam, Abdullah Y.; Joarder, Amina; Cruz-Marcelino, Nerissa; Mitra, Biswadev; Alshehri, Saleh; Almazroua, Faisal
Highlights: There was substantial burden of severe burns in the KSA. Burns injury mostly occurring at home, among males and sustained from flames. Unique resuscitative strategies for inhalation injury require prioritisation. Population-based education programs are indicated to reduce burn injuries. Abstract: Background: Pediatric burn injury is one of the major causes of mortality and morbidity in the Kingdom of Saudi Arabia (KSA). Among survivors, long-term morbidity may have substantial impact. This study aimed to describe the epidemiology of pediatric patients admitted to the burns ICU at King Saud Medical City (KSMC) over a 10-year period. Methodology: This was a retrospective cohort study and included all admitted patients to the burn ICU aged 0–14 years from January 2009 to December 2018. Explicit chart review of medical records was performed to extract demographics, Glasgow Coma Scale (GCS) on arrival, mechanism and extent of injury and in-hospital outcomes. Results: There were 787 pediatric patients admitted in burn ICU over a period of 10 years. Of these, 56.4% were males and 54.7% were Saudi nationals. Most (73.8%) of injuries occurred at home, with 77% occurring were when the child was playing, and 81% were sustained from open flames. Most patients (757, 96%) admitted to the ICU were intubated with 499 (63.4%) diagnosed with inhalation injury. Patients spent an average of 12.6 (4.7) days in the burn ICU. There were 199 (25.3%) deaths at hospital discharge, and among patients discharged alive, 37.1% were discharged to inpatient rehabilitation. Conclusion: There was substantial burden of severe burns in the KSA with majority secondary to flame injury and mostly occurring at home. Inhalation injury was common and indicates requirement for focused education on resuscitative strategies. Population-based education programs are indicated to reduce burn injuries and should be targeted to domestic settings in in the KSA.